Inorganic carbon loading as a primary driver of dissolved carbon dioxide concentrations in the lakes and reservoirs of the contiguous United States. Issue 2 (3rd April 2013) - McDonald, Cory P.; Stets, Edward G.; Striegl, Robert G.; Butman, David
Abstract [1] Accurate quantification of CO2 flux across the air‐water interface and identification of the mechanisms driving CO2 concentrations in lakes and reservoirs is critical to integrating aquatic systems into large‐scale carbon budgets, and to predicting the response of these systems to changes in climate or terrestrial carbon cycling. Large‐scale estimates of the role of lakes and reservoirs in the carbon cycle, however, typically must rely on aggregation of spatially and temporally inconsistent data from disparate sources. We performed a spatially comprehensive analysis of CO2 concentration and air‐water fluxes in lakes and reservoirs of the contiguous United States using large, consistent data sets, and modeled the relative contribution of inorganic and organic carbon loading to vertical CO2 fluxes. Approximately 70% of lakes and reservoirs are supersaturated with respect to the atmosphere during the summer (June–September). Although there is considerable interregional and intraregional variability, lakes and reservoirs represent a net source of CO2 to the atmosphere of approximately 40 Gg C d–1 during the summer. While in‐lake CO2 concentrations correlate with indicators of in‐lake net ecosystem productivity, virtually no relationship exists between dissolved organic carbon and pCO2, aq. Modeling suggests that hydrologic dissolved inorganic carbon supports pCO2, aq in most supersaturated systems (to the extent that 12% of supersaturated systems simultaneously exhibit positive net ecosystem productivity), and also supports primary production in most CO2‐undersaturated systems. Dissolved inorganic carbon loading appears to be an important determinant of CO2 concentrations and fluxes across the air‐water interface in the majority of lakes and reservoirs in the contiguous United States.